2022
DOI: 10.1002/ente.202200472
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Carbon as Conductive Additive to Improve the High‐Rate Charge/Discharge Capacity of Lithium‐Ion Batteries

Abstract: The infiltration ability of electrolytes in to the electrode is vital to the high‐rate charge/discharge capacity of lithium‐ion batteries (LIBs). Herein, mesoporous carbon is used with abundant and continuous mesoporous channels as the conductive additive in LIBs to enhance the infiltration of electrolytes. The Li+ diffusion coefficient of the mesoporous carbon is 1.65 × 10−9 cm s−1, much higher than that of carbon nanotubes (2.5 × 10−10 cm s−1) and carbon black (1.6 × 10−10 cm s−1). It is demonstrated that Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…This is because the rich pore structure of MC−MA fills part of active material so that it has a larger specific capacity, which is similar to other research reports. 10,14,15,24 From the dQ/dV curve in Figure 6b, it can be seen that MC−MA and CC−CA are basically the same during the charge and discharge process, but the reduction peak of CC−CA tends to move to a low voltage direction during the discharge process, and the distance between oxidation peak and reduction peak increases, indicating that CC−CA is more polarized during charge and discharge process. 25 In addition, compared with MC−MA, the reduction peak intensity of CC− CA is weakened, indicating that the capacity released by CC− CA is smaller than that of MC−MA, 26 which is consistent with the results of the charge−discharge curve.…”
Section: Storage Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the rich pore structure of MC−MA fills part of active material so that it has a larger specific capacity, which is similar to other research reports. 10,14,15,24 From the dQ/dV curve in Figure 6b, it can be seen that MC−MA and CC−CA are basically the same during the charge and discharge process, but the reduction peak of CC−CA tends to move to a low voltage direction during the discharge process, and the distance between oxidation peak and reduction peak increases, indicating that CC−CA is more polarized during charge and discharge process. 25 In addition, compared with MC−MA, the reduction peak intensity of CC− CA is weakened, indicating that the capacity released by CC− CA is smaller than that of MC−MA, 26 which is consistent with the results of the charge−discharge curve.…”
Section: Storage Stabilitymentioning
confidence: 99%
“…LIFBs are mainly composed of positive electrode, negative electrode, electrolyte, separator, and auxiliary materials. Cathode materials, , anode materials, electrolytes, , separator, , auxiliary material, tab design, structure design, and so on can improve the rate performance of LIFBs.…”
Section: Introductionmentioning
confidence: 99%
“…However, these approaches have not directly improved Li-ion diffusion within the matrix of the cathode materials. While using a significant electrolyte/electrode ratio could promote the diffusion of Li-ion from the bulk phase of electrolyte to the interface of cathode material during high-rate discharge, it comes at the expense of compromising the energy density and substantially increasing the cost of the devices [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, efforts have been made to employ mesoporous materials as fillers to enhance the performance of batteries, catalysts, adsorbents, gels, and other materials. [32][33][34][35][36][37][38][39] Previous studies have also reported the incorporation of other inorganic nanomaterials (nanosilica, calcium carbonate, etc.) into gels, which either improve the strength of the gels/adhesives or give them other properties (antibacterial, anti-inflammatory, etc.).…”
Section: Introductionmentioning
confidence: 99%